Importance of Marketing Activities in a Company: the Management Perspective - Urbonavičius, Sigitas; Dikčius, Vytautas (Ekonomika, 2008)
The article analyses how managers of companies see the importance of the overall marketing function as the importance of certain types of marketing activities. These types include typical areas of 4 Ps as well as marketing planning and marketing research activities. The research is based on a survey of 205 managers of primarily manufacturing and trading companies that operate in Lithuania.Managers evaluated marketing planning and distribution as the most important marketing functions, while marketing research and price management appeared to be significantly less important. Some differences of evaluations were observed on the basis of characteristics of companies. Managers of larger companies see the advantages of marketing planning and marketing research, managers of subsidiaries of international corporations evaluated four types of marketing activities significantly higher than did managers of independent companies. A lot of differences in evaluations were observed, depending on the key priority of the company strategy.Data also showed a positive relationship between the evaluations of marketing activities and company growth. Though the growth is obviously influenced by numerous other factors, this relationship proves the significance of the marketing function in achieving better business results.